Nocturnal metiamide treatment in the management of healed duodenal ulceration. Issue 6 (June 1977) - Thompson, M H; Venables, C W; Smith, P A; Walker, W
Abstract : This paper presents the results of a pilot study to investigate whether the administration of a nocturnal dose of metiamide (the first orally active H2 receptor antagonist) would prevent or delay the relapse of duodenal ulceration after initial ulcer healing. Sixteen patients took part in a double-blind trial to compare metiamide (400 mg) with placebo. Endoscopically confirmed duodenal ulcer relapses occurred in two out of eight on metiamide and six out of eight on placebo. There was a significant prolongation of remission in those in those on the active drug with an apparent reduction in duodenitis.